An analysis of labor and capital productivity in the Malaysian timber sector - Ratnasingam, Jegatheswaran; Chin, Khoon Ark; Mohamed, Shukri; Lim, Choon Liat; Ramasamy, Geetha; Senin, Abdul Latib (North Carolina State University, 2017)
The remarkable transformation of the Malaysian timber sector from a net-importer to a multi-billion-dollar export-oriented sector has become a success model for many other resource-rich countries throughout the world. In view of the increasing socioeconomic importance of the timber sector in this country, the productivity performance of the six major timber sub-sectors was investigated in this study. Productivity is defined as the ratio of output to input and was analyzed from the year 2010 through 2014. The productivity performance was evaluated based on certain input factors, namely labor and capital. Generally, the productivity of the timber sector can be regarded as stagnating. Furthermore, the value-added was affected due to high reliance on labor for production. Among the factors that account for this lack of productivity growth are the increased competition in the international market, small domestic market, improper industrial development policies, poor adoption of technology, and the high dependency on human capital.